2017
DOI: 10.1186/s13578-017-0142-x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of LSD1 by PLK1 promotes its chromatin release during mitosis

Abstract: BackgroundLysine-specific histone demethylase 1 (LSD1) modulates chromatin status through demethylation of H3K4 and H3K9. It has been demonstrated that LSD1 is hyperphosphorylated and dissociates from chromatin during mitosis. However, the molecular mechanism of LSD1 detachment is unknown.ResultsIn this report, we found that polo-like kinase 1 (PLK1) directly interacted with LSD1 and phosphorylated LSD1 at Ser-126 . Nocodazole-induced metaphase arrest promoted release of LSD1 from chromatin, and the phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…However, a serious concern is raised that no differences in the global levels of H3K4 methylation, including H3K4me1, H3K4me2 or H3K4me3, were observed between the control and Setd1b null oocytes and zygotes ( Brici et al, 2017 ). This is in sharp contrast to the Cxxc1 null oocytes, in which the H3K4me3 level decreases significantly ( Yu et al, 2017 ; Sha et al, 2018a ). Therefore, these results suggest two facts, i.e., ( Dai et al, 2018 ) SETD1A and SETD1B play overlapping roles in mediating H3K4 trimethylation during oogenesis, whereas CXXC1 is indispensable as a DNA-binding subunit of the SETD1/CAMPASS complex, and ( Sha et al, 2018b ) the absence of SETD1B may affect the distribution— instead of the global abundance—of H3K4m3 in the maternal genome and cause milder defects than the Cxxc1 knockout in oocytes.…”
Section: Function Of Histone H3k4 Methyltransferases In Oogenesis Andmentioning
confidence: 92%
See 2 more Smart Citations
“…However, a serious concern is raised that no differences in the global levels of H3K4 methylation, including H3K4me1, H3K4me2 or H3K4me3, were observed between the control and Setd1b null oocytes and zygotes ( Brici et al, 2017 ). This is in sharp contrast to the Cxxc1 null oocytes, in which the H3K4me3 level decreases significantly ( Yu et al, 2017 ; Sha et al, 2018a ). Therefore, these results suggest two facts, i.e., ( Dai et al, 2018 ) SETD1A and SETD1B play overlapping roles in mediating H3K4 trimethylation during oogenesis, whereas CXXC1 is indispensable as a DNA-binding subunit of the SETD1/CAMPASS complex, and ( Sha et al, 2018b ) the absence of SETD1B may affect the distribution— instead of the global abundance—of H3K4m3 in the maternal genome and cause milder defects than the Cxxc1 knockout in oocytes.…”
Section: Function Of Histone H3k4 Methyltransferases In Oogenesis Andmentioning
confidence: 92%
“…In addition to MZT defects, meiotic resumption and spindle assembly are impaired in fully grown Cxxc1 -deleted oocytes ( Yu et al, 2017 ; Sha et al, 2018a ). The involvement of CXXC1 and H3K4me3 in the regulation of meiotic cell cycle progression is discussed in later sections.…”
Section: Function Of Histone H3k4 Methyltransferases In Oogenesis Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies established that LSD1 activity and stability is altered by post-translational modifications [40,41] . LSD1 is acetylated in epithelial, but not in mesenchymal cells.…”
Section: Lsd1 Post-translational Targeting In Emt Modulationmentioning
confidence: 99%
“…Finally, several studies reported that KDM1A is subjected to different post-translational modifications, which may alter its activity or stability [86,87]. It has been shown that acetylation of KDM1A by KAT8/MOF impairs KDM1A ability to associate with nucleosomes, resulting in enhanced expression of epithelial genes and suppressing epithelial-to-mesenchymal transition [88].…”
Section: Regulation Of Kdm1a/lsd1 During Autophagymentioning
confidence: 99%